Etched fiber Bragg grating sensor for nitrate sensing application - Mohd Razali, Nazirah; Ambran, Sumiaty; Hamzah, Azura; Abdullah, Norhayati; Mikami, Osamu; Hara, Hirofumi; Lokman, Mohammad Quisar; Yaacob, Mohd Hanif (IEEE, 2018)
We demonstrate a reliable method to detect the concentration of Nitrate in water using an etched Fiber Bragg Grating (FBG) sensor. The sensor was etched using 48% Hydrofluoric (HF) acid solution to function as a chemical sensor and interact with Nitrates. The Bragg wavelength (λb) shifted due to the changes of Nitrate concentration. The sensitivity achieved by this sensor is 2.4 × 10-3 nm/ppm. The overall shift of the Bragg wavelength is 0.12 nm from 0 - 50 ppm.